Crack propagation behavior of solution annealed austenitic high interstitial steels. (October 2015) - Schymura, Michael; Stegemann, Robert; Fischer, Alfons
Highlights: AHIS provide crack propagation rates (CPR) one order of magnitude smaller compared to CrNi-ASS. The most favorable combination of CPR and σD lies between 0.85 and 0.96 (C+)N wt.%. Increase of interatomic short range order brought by (C+)N content allows only for planar slip. Increase of interatomic short range order brought by (C+)N content contributes to the improved CPR. Abstract: Austenitic stainless steels provide a beneficial combination of chemical and mechanical properties and have been used in a wide field of applications for over 100 years. Further improvement of the chemical and mechanical properties was achieved by alloying nitrogen. But the solubility of N within the melt is limited and can be increased in substituting Ni by Mn and melting under increased pressure. In order to avoid melting under pressure and decrease production costs, a part of N can also be substituted by C. This leads to austenitic high interstitial steels (AHIS). Within the solution annealed state strength and ductility of AHIS is comparable or even higher of those of AHNS and can be further improved by cold working. Unfortunately the endurance limit does not follow this trend as it is known from cold-worked austenitic CrNi steels. This is due to the differences of the slip behavior which is governed by the stacking fault energy as well as other near field effects. Construction components operating under cyclic loads over long periods of time cannot be considered being free of voids or even cracks. Thus the crack propagation behavior is of strong interest as well. This contribution presents the tensile, fatigue, crack propagation and fracture toughness properties of AHNS and AHIS in comparison to those of CrNi-steels. The differences are discussed in relation to microstructural characteristic as well as their alterations under cyclic loading.